DEVELOPMENT OF VIDEO LEARNING MEDIA FOR THE TRADITIONAL MANGGARAI DANCE “TIBA MEKA” TO IMPROVE THE DANCE SKILLS OF EIGHTH GRADE JUNIOR HIGH SCHOOL STUDENTS: DEVELOPMENT OF VIDEO LEARNING MEDIA FOR THE TRADITIONAL MANGGARAI DANCE “TIBA MEKA” TO IMPROVE THE DANCE SKILLS OF EIGHTH GRADE JUNIOR HIGH SCHOOL STUDENTS - eldi, reineldis putri; Mariasa, I Nengah (Solah, 2025)
The development of video learning media was carried out as an innovative effort to provide more interesting and varied learning tools for student, considering that previous learning media were unable to stimulate interest in learning. The development of media was also carried out to overcome the limitations of arts and culture teachers in the Manggarai region so that the learning process could run independently and more effectively through the presentation of material in a visual and structured manner. The purpose of this study was to develop learning media in the form of Tiba Meka dance videos, which are traditional dances from the Manggarai region, to improve the dancing skills of eighth-grade junior high school students. This initiative was taken as an effort to improve students’ abilities through the use of video-based learning media. The researcher used the ADDIE research and development method, which has five main stages: Analysis, Design, Development, Implementation, and Evaluation. The data collection techniques applied in this study include field observations, interviews, guestionnaire distribution, and documentation. Data analysis was conducted qualitatively for observation and interview data, and quantitatively for questionnaire data measured through score acquisition. The research instrument used included validation sheets fpr axperts, as well as response questionnaires from students and teachers. The media development process, which was carried out using ADDIE based on an analysis of student needs, curriculum analysis, and student characteristic, demonstrated success in the creation of learning media. The feasibility test, which involved validation by subject matter experts, media experts, and teacher feedback, showed that the media falls into the highly feasible category, while the practicality test conducted by students and teachers indicated that the media is practical. Thus, the results of the research on the develop of Tiba Meka dance video learning media are effective in improving the dance skills of eighth-grade junior high school students.